Factors Associated with Acute Telogen Effluvium and COVID-19 Infection - Nawab, Faryal; Zameer, Farina; Ahmed, Salman; Hanif, Tooba; Awan, Nimrah Sarwar; Aman, Shahwaiz (Indus Journal of Bioscience Research, 2025)
Telogen effluvium, a common type of hair loss, has emerged as a concerning side effect for many individuals recovering from COVID-19. Methodology: A descriptive cross-sectional study was conducted at Dermatology Outpatient department of Sohail Trust Hospital, Karachi to determine frequency and factors associated with Acute telogen effluvium and COVID-19 infection. We enrolled 100 Covid 19 PCR positive patients between January to July 2022 after taking informed consent. This study employed a semi-structured self-administered questionnaire for data collection. Statistical analyses were conducted using SPSS version 25. The Chi-square test was utilized to assess the association between Telogen Effluvium and COVID-19 infection. Multivariable logistic regression analyses were performed to identify factors associated with the development of Telogen Effluvium. Results: Our findings revealed that 64% of female participants experienced Telogen Effluvium following COVID-19 infection. Diabetes emerged as the most prevalent co-morbidity among these patients. The temporal region was the most frequently affected scalp area (32%), followed by complete hair loss observed in 31% of cases. Participants who did not supplement their diets were significantly more likely to experience severe hair loss. Notably, 34.6% of individuals with hair loss reported that other family members also developed hair loss post-COVID-19. Within our study population, only 7% sought professional treatment for their hair loss. Conclusion: This study demonstrates a high prevalence of Telogen Effluvium among female COVID-19 survivors, with diabetes as a significant risk factor, highlighting the need for increased awareness and accessible treatment options for this undertreated condition.